If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -11 = 6n + 5 Reorder the terms: -11 + 4n = 6n + 5 Reorder the terms: -11 + 4n = 5 + 6n Solving -11 + 4n = 5 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. -11 + 4n + -6n = 5 + 6n + -6n Combine like terms: 4n + -6n = -2n -11 + -2n = 5 + 6n + -6n Combine like terms: 6n + -6n = 0 -11 + -2n = 5 + 0 -11 + -2n = 5 Add '11' to each side of the equation. -11 + 11 + -2n = 5 + 11 Combine like terms: -11 + 11 = 0 0 + -2n = 5 + 11 -2n = 5 + 11 Combine like terms: 5 + 11 = 16 -2n = 16 Divide each side by '-2'. n = -8 Simplifying n = -8
| 32y^2-10y+1=0 | | Y^2-18y=-81 | | X-3+x-3=x+6 | | 1+2x-x=x+5+x | | -32+2z=5(8z-9) | | 65=25-8k | | 31=9(7h-6) | | 12x^5y^3z+6x^2yz^4= | | 6x+34=424 | | K+50=9k-4 | | 206=8-6(-6x+3) | | 8-(-2.5)= | | 7x^2+4xy+4y^2=57 | | 1.5x+9-4.5x=6 | | 11-2a=3a-14 | | -16=-8x-4 | | 2x+4-x=-17 | | 9x-21-5x=31 | | 11(n-2)=-11(1-n) | | 16=-8x-4 | | 6-7a-2n-8= | | 11h+6= | | ln(3)+ln(9)=x | | 0.7x+0.4=-1 | | 4(4x+2)+5=16x+13 | | 2x=4(1.50) | | 3(x-4)+3(x-2)=0 | | -9y-3=3 | | 56=8xp | | 9x+4y=172 | | 7k+3-6k=-35 | | X+2*2=3x-8 |